Bromide-Assisted Anisotropic Growth of Gold Nanoparticles as Substrates for Surface-Enhanced Raman Scattering - Kerr, Melissa A.; Yan, Fei (Journal of Spectroscopy, 2016)
We report herein a one-step synthesis of gold nanoparticles (Au NPs) of various shapes such as triangles, hexagons, and semispheres, using 5-hydroxyindoleacetic acid (5-HIAA) as the reducing agent in the presence of potassium bromide (KBr). Anisotropic Au NPs have received ever-increasing attention in various areas of research due to their unique physical and chemical properties. Numerous synthetic methods involving either top-down or bottom-up approaches have been developed to synthesize Au NPs with deliberately varied shapes, sizes, and configurations; however, the production of templateless, seedless, and surfactant-free singular-shaped anisotropic Au NPs remains a significant challenge. The concentrations of hydrogen tetrachloroaurate (HAuCl4), 5-HIAA, and KBr, as well as the reaction temperature, were found to influence the resulting product morphology. A detailed characterization of the resulting Au NPs was performed using ultraviolet-visible (UV-Vis) spectroscopy, scanning electron microscopy (SEM), and Raman spectroscopy. The as-prepared Au NPs exhibited excellent surface-enhanced Raman scattering (SERS) properties, which make them very attractive for the development of SERS-based chemical and biological sensors.